Diverse Mechanisms of Protective Anti-Pneumococcal Antibodies - Gingerich, Aaron D.; Mousa, Jarrod J. (Frontiers in Cellular and Infection Microbiology, 2022)
The gram-positive bacterium Streptococcus pneumoniae is a leading cause of pneumonia, otitis media, septicemia, and meningitis in children and adults. Current prevention and treatment efforts are primarily pneumococcal conjugate vaccines that target the bacterial capsule polysaccharide, as well as antibiotics for pathogen clearance. While these methods have been enormously effective at disease prevention and treatment, there has been an emergence of non-vaccine serotypes, termed serotype replacement, and increasing antibiotic resistance among these serotypes. To combat S. pneumoniae, the immune system must deploy an arsenal of antimicrobial functions. However, S. pneumoniae has evolved a repertoire of evasion techniques and is able to modulate the host immune system. Antibodies are a key component of pneumococcal immunity, targeting both the capsule polysaccharide and protein antigens on the surface of the bacterium. These antibodies have been shown to play a variety of roles including increasing opsonophagocytic activity, enzymatic and toxin neutralization, reducing bacterial adherence, and altering bacterial gene expression. In this review, we describe targets of anti-pneumococcal antibodies and describe antibody functions and effectiveness against S. pneumoniae.